Retornos en salud de la población adulta mayor - Cortez, Rafael (2002)
The oldest people is described as one of the most vulnerable population groups in the country. They require special public attention since there is a weak protection to risks and external changes. The demographic transition in Peru is increasing the proportion of people older than 60 years in a constant pattern. Besides, labor participation is high around 54%, and poverty levels even higher (70%). The objective of the study is to estimate the impact of health status on labour productivity in the older people in Peru. The findings confirm the importance of the health status on productivity. The health return rate is higher in rural women compare to other groups. In summary, the health status of the older people is a key factor determining the level of their labour productivity. The calculation of the health rate of returns by urban/rural and gender provides useful information for the design of further social investment strategies to target resource allocation in favour of the analysed vulnerable group.